The Proper Use of Talent Management - Abarca-Achig, Maritza Catalina (2021)
In order to properly cover the article’s objective, it is necessary to agree that the term human talent is inappropriate, considering that only humans have talent. The approach points out that the organizations who aspire to effectively develop their talents, will have to sustain their efforts in actions such as; counting with qualified candidates, implementing a good work environment, adequate communication, pride of belonging, to provide their collaborators with autonomy to manage, stablishing new challenges, having an objective subsystem of performance evaluation and, lastly, rewards which retain the best talents. For this, bibliographic researches inherent to the topic were made, with the purpose to contrast the empirical application of this work, with the application of the required proposed actions, both in short, and in long time. The results support the posed hypothesis, for what is faculty of the organizations’ administration at the time of making decisions, to guarantee the application of a planned methodological process taking as source of bibliographic information other articles inherent to the topic combined with field research through consultations with experts planned to successfully implement a management strategy in pro of the organizational development. This input is sustained on an investigation that collects and organizes bibliographic data. It should be concluded that the most important element in the organization is an empowered talent who feels that their help is their life project.